Comprehensive Study on Phased Antenna Array Based on Conventional and Shielded Butler Matrix for 2.4 GHz Applications - Haidar, Muhannad Basem (Eastern Mediterranean University EMU, 2017)
In this work, a phased antenna array based on 4×4 Butler matrix is designed and simulated for 2.4 GHz applications using Roger RT 5880 as a substrate layer. CST SUIT STUDIO is used for this purpose. Two different designs of phased antenna array are simulated; the first one was based on microstrip technology, which is used to design both the feeding network (Butler matrix) and antenna array. The objective is achieved by switching the main beam to ±14̊ and ±40̊. The side lobe levels of -9.4dB and -8.2dB were obtained while the directivities were 12.4dBi and 11.5dBi when different input ports were applied. The physical size of the overall structure is about 621 cm2. An enhancement on antenna radiation pattern is obtained by using a strip line instead of microstrip line in the design of the Butler matrix. The antenna array is shielded at the top layer of the structure from the spurious radiation of Butler matrix radiation effect. The radiation pattern is obtained by making square slits on the top layer of the ground plane. The side lobe levels are reduced by 2.8dB and 0.3dB while the directivity is increased. The proposed design has deeper nulls and smaller physical size. The overall structure size is about 436.6 cm2. The scanning angle directions does not change compared with the conventional design based on microstrip technology since the spacing between antenna elements is the same in both cases. Keywords: Phased Antenna Array, Butler Matrix, Strip line, Shielded Antenna.

ÖZ: Bu çalışmada, Roger RT 5880 katmanı kullanılarak 2.4 GHz uygulamaları için 4×4 Butler matrisine dayalı fazlı anten dizisi tasarlanmış ve sonuçlar CST SUIT STUDIO benzetim yazılımı ile elde edilmiştir. Fazlı anten dizi sistemi iki farklı tasarımda ele alınmıştır. Birinci tasarımda hem besleme ağı, hem de dizi anten, mikro şerit teknolojisi kullanılak elde edilmiştir. Amaçlandığı gibi ±14 ° ve ±40 ° yönlerinde, dört hüzme elde edilmiştir. Elde edilen ışıma deseninin yan lopları -9.4dB ve -8.2dB düzeylerindedir. Buna karşılık yönlendirmeler, farklı besleme noktaları kullanıldığında 12.4dBi ve 11.5dBi seviyelerindedir. Toplam yapının fiziksel boyutu yaklaşık 621 cm2’dir. Butler matrisinin tasarımında, mikro şerit hattı yerine şerit hattı kullanılması, Butler matrisinin besleme devresinden kaynaklanan sanal ışıma etkisinin izole edilmesine ve antenin ışıma yaratacak yapısının üst katmanda kalarak ışıma deseninde bir iyileşme elde edilmesine sebep olmuştur. Işıma deseni, zemin düzleminin üst katmanında kare kesikler yaparak elde edilmiştir. Yan lob seviyeleri 2.8dB ve 0.3dB azaltılırken, yönlendirilmede artış elde edilmiştir. Önerilen tasarım daha derin boşluklara ve daha küçük fiziksel boyutlara sahiptir. Toplam yapı boyutu yaklaşık 436.6 cm2. Anten elemanları arasındaki mesafe her iki durumda da eşit olarak alındığından tarama açıları değişim göstermemiştir. Anahtar Kelimeler: Fazlı anten dizisi, Butler matrisi, şerit hattı, korunaklı antyen.
Master of Science in Electrical and Electronic Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Electrical and Electronic Engineering, 2017. Supervisor: Assist. Prof. Dr. Rasime Uyguroğlu.
Keywords: Electrical and Electronic Engineering; Antennas (Electronics); Wireless Communication Systems-Adaptive Antennas-Smart Antennes; Phased Antenna Array; Butler Matrix; Strip line; Shielded Antenna